A Theoretical Examination of Shadow Education in South Korea - Natalie-Jane Howard (International Journal of Asian Education, 2021)
This article provides a theoretical contribution to the contemporary debates regarding the legitimacy and effects of supplementary tutoring, also known as shadow education. Shadow education is notably pervasive in South Korea, and accounting for high rates of domestic expenditure and increasing time demands on young people’s lives.  The paper traces the historical and cultural reasons for the widespread uptake of shadow education amongst young students in the South Korean context and problematises what it means to be educated by juxtaposing leading scholars’ perceptions of the fundamental aims of education. Delving into the reality of shadow education whilst also revealing the disruptive nature of this common place practice, the paper concludes by highlighting the need for further empirical research to counterbalance the largely unsubstantiated beliefs and anecdotal evidence regarding its purposes